Mechanisms of spur and groove development and implications for reef platform evolution. (1st March 2020) - Duce, Stephanie; Dechnik, Belinda; Webster, Jody M.; Hua, Quan; Sadler, James; Webb, Gregory E.; Nothdurft, Luke; Salas-Saavedra, Marcos; Vila-Concejo, Ana
Abstract: Contemporary understanding of Holocene coral reef development is based primarily on sub-surface investigations of reef flat, back reef and lagoon zones. Few studies of Holocene fore reef development exist, constituting a significant gap in our understanding of reef evolution. The spur and groove (SaG) zone is a distinct, understudied, feature of fore reefs worldwide. We review SaG development from previous studies and present 29 new SaG short cores with 52 14 C and U–Th ages from six fore reef regions of Heron and One Tree reefs, the first such data from the Great Barrier Reef. Remarkably, we found that SaGs do not necessarily accrete in the same direction as their adjacent reef flat. We identified three modes of reef flat and SaG lateral accretion: Mode 1 – lagoonward accretion of both the reef flat and SaGs; Mode 2 –lagoonward accretion of the reef flat but seaward accretion of the SaGs; Mode 3 - seaward accretion of both the reef flat and SaGs. Most SaG zones (five of the six studied) accreted in a seaward direction (Modes 2 or 3). Hydrodynamic conditions and local topography appear to be the dominant factors determining which mode occurs. Episodic high-energy events are also likely to play an important role in SaG formation. Our findings suggest that traditionally held models of reef evolution whereby lagoonal, mature reefs fill, developing into senile platform reefs, may not hold. Rather, reef flats may continue to expand seaward on their leeward, and semi-exposed fronts to increase in size while maintaining their lagoons. Highlights: Cores show 3 modes of spur and groove development in southern Great Barrier Reef. Hydrodynamic conditions and local topography likely determine which mode occurs. Episodic high-energy events also play an important role in formation. Most spur and groove zones cored were accreting seaward. Reef flats may continue to expand seaward while maintaining their lagoons.